Pengaruh Permainan Lempar Tangkap Bola Kecil Terhadap Kemampuan Koordinasi Mata Dan Tangan Siswa Kelas V SDN Johar Baru 15 - Khamilah, Nasywa Shafa (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This research aims to determine influence of small ball throwing catching game on eye-hand coordination ability of grade V students at SDN Johar Baru 15. The method used is Quasi-Experiment Design with a Pretest-Posttest Control Group. Population in the study 60 students, of which 48 student were selected as samples and divided equally into experimental and control groups. The instrument used to measure eye hand coordination is test coordination eye hand, while data analysis was conducted with normality tes, homogeneity tests, and hypothesis testing. Based on the resulst of the normality tests using the Shapiro-Wilk normalty test indicate that the pretest and posttest data from both groups have significance values >0.05. Specifically, the pretest significance group experimental value was 0.723 for the group control pretest value was 0.122. While the significance the posttest group experimental value was 0.555 for the group control value was 0.357. That result the data is distributed normally. The result of homogeneity using Levene's statistic stated that pretest significance of 0.786, and significance value of the posttest 0.702, this indicates both >0.05 homogenity distributed data. Hypothesis test used paired sample t-test yielded a p value (0.000) <0.05. Thus,it can be conclusion that the small ball throwing catching game influence eye hand coordination ability of students at SDN Johar Baru 15.